Cognate therapy for developmental language dis-orders (DLDs) in multilingual settings - Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2017)
Authors Maria Kambanaros, Department of Rehabilitation Sciences, School of Health Sciences, Cyprus University of Technology, Limassol, Cyprus Background Clinicians globally recognise as exceptionally challenging the development of effective intervention practices for bi- or multilingual children with DLDs. Therapy in both or all of an impaired child’s languages is most often rarely possible. An alternative is to develop treatment protocols that facilitate the transfer of therapy effects from a treated language to an untreated language. Aims The aim of this study is to explore whether cognates, words that share meaning and phonological features across languages, could be used to boost lexical retrieval in the context of multilingual DLD. Methods & Procedures The participant is an 8.5-year-old girl diagnosed with SLI who showed a severe naming deficit in her three spoken languages (Bulgarian, English, and Greek). She received training on cognates (n=20) using a picture-based naming task in English only, three times a week, over a four-week period for 20 minutes each time. Phonological-based naming therapy was carried out using form-based strategies. Results There was a significant improvement during and immediately after intervention on cognate performance in English that was maintained one month after intervention. Cognate production in Bulgarian and Greek also improved during all phases of the intervention. Conclusions & Implications Cross-linguistic transfer effects were evident during and after treatment, and they were maintained one month post treatment. Generalisation to non-treatment words was evident, only for English, the treated language. The results suggest that cognates can be used successfully as a vocabulary training strategy for multilingual children with DLDs with lasting effects.
Keywords: Cognates; Words; Lexical retrieval; Multilingual DLD